Proceedings of the 3rd World Sustainability Forum 2013
DOI: 10.3390/wsf3-b001
|View full text |Cite
|
Sign up to set email alerts
|

EMAS Regulation in Italian Clusters: Investigating the Involvement of Local Stakeholders

Abstract: Abstract:The last revision of the EMAS Regulation encouraged a cluster approach to increase the participation of the organizations and to involve local stakeholders in the sustainability process. Our research activity, conducted by the Department of Business Studies of Roma Tre University and ISPRA (High Institute for Environmental Protection and Research), intends to partially fill the literature gap in the field by investigating the Italian cluster approach for EMAS, characterized by the creation of a cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Italy also experimented a cluster-based approach to EMAS, which allowed industrial clusters to obtain recognition with an EMAS certificate. This approach promoted the diffusion of the scheme in single organizations and made local stakeholders more aware of the scheme [41,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Italy also experimented a cluster-based approach to EMAS, which allowed industrial clusters to obtain recognition with an EMAS certificate. This approach promoted the diffusion of the scheme in single organizations and made local stakeholders more aware of the scheme [41,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be emphasised that the previous research concerning the effects of EMAS implementation focused mainly on determining whether and what general environmental effects were achieved by the companies after participating in the system. The research shows that most frequently indicated benefits concerned systematisation and arrangement of previous environmental activities (Freimann, Schwaderlapp, 1996;Hillary, 1998 ), limiting the negative environmental impact mainly through the reduction of generated waste and the usage of resources and energy (Bültmann, Wätzold, 2000;Schucht, 2000;Umweltbundesamt, 2000;Braun, Grotz, 2002;Wenk, 2004;Hyršlova, Hajek, 2006;Vernon et al, 2009;Nycz-Wróbel, 2016a) and also improvement of environmental performance (Hillary, 1998;Morrow, Rondinelli, 2002;Hillary, 2004;Daddi et al,2011;Merli et al, 2014; Nycz-Wróbel, 2016a). More specific activities planned or implemented in order to improve environmental performance have been indicated in the research conducted among German and French companies.…”
Section: Review Of Previous Research Concerning Emasmentioning
confidence: 99%